Comparing the Utilization of Cocopeat and Topsoil Planting Media with Cow Manure Fertilizer on Chili Peppers' (Capsicum frutescens) Growth - Agung Arya, Dimas; Walida, Hilwa; Dalimunthe, Badrul Ainy; Sepriani, Yusmaidar (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Chili pepper (Capsicum frutescens) is one of the important horticultural commodities in Indonesia, widely cultivated due to its spicy flavor and high economic value. This study aims to compare the effectiveness of various planting media and fertilizers in promoting the environmentally friendly growth of chili pepper plants. The study employed a Factorial Randomized Block Design (RAK) with treatments including: Control (without cow manure), 2 kg of cocopeat and 1 ounce of cow manure, 2 kg of cocopeat and 1.5 ounces of cow manure, 2 kg of cocopeat and 2 ounces of cow manure, 2 kg of soil and 1 ounce of cow manure, 2 kg of soil and 1.5 ounces of cow manure, and 2 kg of soil and 2 ounces of cow manure. Data analysis was conducted using ANOVA and BNT post-hoc tests. The results showed that the planting media did not significantly affect plant height or the number of leaves, though variations in values were observed across treatments. In cocopeat media, the treatment of 2 kg of cocopeat and 1.5 ounces of cow manure resulted in the highest plant height at week 4, measuring 30.03 cm, followed by 2 kg of cocopeat and 1 ounce of cow manure (29.23 cm), 2 kg of cocopeat and 2 ounces of cow manure (29.20 cm), and the control treatment (28.46 cm). The highest number of leaves was also found in the 2 kg of cocopeat and 1.5 ounces of cow manure treatment, with 16.66 leaves, although in the second week, the control treatment recorded only 6.33 leaves. In soil media, the 2 kg of soil and 2 ounces of cow manure treatment produced 17.66 leaves, with variations in the second week noted between the cow manure treatments and the control group.